Incidence of retinopathy of prematurity in Lothian, Scotland, from 1990 to 2004. Issue 6 (7th May 2008) - Dhaliwal, C; Fleck, B; Wright, E; Graham, C; McIntosh, N
Abstract : Background: To report the trends in incidence of retinopathy of prematurity (ROP) within Lothian, a geographically defined region in southeast Scotland over a 15-year period from 1990 to 2004. Methods: This was a prospective observational study of all infants born with gestational age <32 weeks and/or birth weight <1500 g who were born to mothers resident in Lothian between 1 January 1990 and 31 December 2004. Eligible infants underwent eye screening by two experienced paediatric ophthalmologists (BF and EW). Lothian population data were obtained from the Scottish Health Service. The trends in survival rates, incidence and treatment of ROP were analysed from 1990 to 1994, 1995 to 1999 and 2000 to 2004. Results: Lothian population data showed a steady decline in the number of live births from 1990 to 2004. The proportion of babies born with birth weight <1500 g and/or gestational age <32 weeks remained constant (p = 0.271 using χ 2 test), although the proportion of these babies surviving to 42 weeks corrected gestation increased from 1990 to 2004 (p<0.001 using χ 2 test for trend). There was a statistically significant linear trend towards a reduction in the number of babies undergoing treatment for ROP throughout the study period (p<0.01 using χ 2 test for trend). A reduction in the incidence of any degree of ROP and severe (stage 3 or greater) ROP was also observed although this did not reach statistical significance. Conclusions: There was a significant increase in survival of infants with birth weight <1500 g and/or gestational age <32 weeks together with a significant reduction in the number of infants treated for ROP in the Lothian region of southeast Scotland from 1990 to 2004.